Strategi Pemasaran Politik Partai Golkar Dalam Pemenangan Pasangan Rahmad Pada Pilkada Bondowoso 2024 - Muhammad Rizal Bintang Firmansyah; Suwignyo Widagdo; Tamriatin Hidayah (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
The purpose of this study is to analyze the political marketing strategy of the Golkar Party in winning the candidate pair Ra Hamid and Ra As'ad (RAHMAD) in the 2024 Bondowoso Pilkada. This research uses a qualitative method with a case study approach. Data were collected through in-depth interviews, observation, and documentation. The results showed that the Golkar Party successfully implemented an integrated strategy of push, pull, and pass marketing. Key success factors include the repositioning of the candidate's religious-intellectual image, a "no-dowry" (tanpa mahar) political policy, and the utilization of Islamic boarding school (pesantren) networks as a local power base. The humanistic and digitalized communication strategy played a crucial role in reaching voters across generations.